2013
DOI: 10.1177/1553350613506299
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Prebent Customized Prosthesis for Pectus Excavatum Minimally Invasive Surgery Correction

Abstract: Pectus excavatum is the most common deformity of the thorax. A minimally invasive surgical correction is commonly carried out to remodel the anterior chest wall by using an intrathoracic convex prosthesis in the substernal position. The process of prosthesis modeling and bending still remains an area of improvement. The authors developed a new system, i3DExcavatum, which can automatically model and bend the bar preoperatively based on a thoracic CT scan. This article presents a comparison between automatic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…The personalized bar was modeled with the system developed by Vilaça et al 32 using the CT data of each patient. The bar shape and size were used to bend the metal bar applied in the surgery and to create the virtual model of the bar used in the FEM simulation.…”
Section: Generation Of the Patient-specific Biomechanical Modelmentioning
confidence: 99%
“…The personalized bar was modeled with the system developed by Vilaça et al 32 using the CT data of each patient. The bar shape and size were used to bend the metal bar applied in the surgery and to create the virtual model of the bar used in the FEM simulation.…”
Section: Generation Of the Patient-specific Biomechanical Modelmentioning
confidence: 99%
“…Traditionally, the length of the pectus bar is determined by measuring the distance between the midaxillary lines with a measuring tape and subtracting 2.5 cm [1]. Although the Nuss procedure has become the standard for surgical PE intervention [2], the size and curvature of the pectus bar are determined by trial and error with repeated insertions and flips of the pectus bar [3][4][5]. These readjustments are bothersome and potentially hazardous.…”
Section: Commentmentioning
confidence: 99%
“…The Nuss procedure, first reported in 1998 by Nuss and associates [1], is the placement of a pectus bar to elevate the sternum anteriorly. Although the Nuss procedure has become the standard of surgical intervention for PE [2], the size and curvature of the pectus bar is determined by trial and error by repeated insertion and flipping of the pectus bar [3][4][5].…”
mentioning
confidence: 99%
“…However, it has been shown that the conventional pectus bar modeling based on the patient's skin profile is imprecise [4]. More recently, the same group evaluated a system simulating the pectus bar, but the design of the bar was not presented [5]. Wei et al developed a biomechanical model of PE based on a finite element model using a single patient CT image [6], but the rib cage used to establish the model was manually segmented.…”
Section: Introductionmentioning
confidence: 98%